Influence of preoperative enema application on the return of gastrointestinal function in elective Cesarean sections: a randomized controlled trial. (3rd June 2021) - Ertas, Ibrahim Egemen; Ince, Onur; Emirdar, Volkan; Gultekin, Emre; Biler, Alper; Kurt, Sefa
Abstract: Aim: There is an extensive literature on the mechanical bowel preparation by an enema in colorectal, abdominal, and gynecologic surgeries that provide evidence against the use of enema. There are, however, few studies investigating the effect of enema prior to elective Cesarean sections. The aim of this study is to investigate whether preoperative enema facilitates the return of gastrointestinal activity in pregnant women undergoing elective Cesarean section. Materials and methods: The surgeon-blinded prospective randomized controlled study included 225 elective Cesarean patients between the ages of 18 and 44. The patients were randomized into two groups: those who had enema preoperatively ( n = 114) and those who did not ( n = 111). The outcome measures were first bowel sound time and first flatus time, the length of hospital stay, the rate of mid ileus symptoms, and additional analgesic and antiemetic need. Results: In the non-enema group, the time of the first bowel sound, flatus time, length of hospital stay, the rates of additional analgesic need, additional antiemetic need, and mild ileus symptoms were respectively 10.5 ± 5.8 hours, 16.0 ± 7.6 hours, 1.9 ± 0.3 days, 8.1%, 7.2%, and 2.7%. For the enema group, the same parameters were respectively 11.6 ± 4.7 hours, 17.5 ± 6.5 hours, 1.8 ± 0.3 days, 7%, 6.1%, and 1.8%. For all parameters, the difference between the groups was not statistically significant ( p values were respectively .09, .12, .8, .79, .68, and .26). Conclusions: The study suggests that preoperative enema in elective cesarean sections does not prevent postoperative gastrointestinal complications and does not shorten the recovery of bowel movements or length of hospital stay.